EFFECT OF ANXIETY AND STRESS ON THE JOB SATISFACTION OF SECONDARY SCHOOL TEACHERS - Singh, Dharmendra; Jain, Vinod Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
In schools, teachers and students are mutually dependent on each other. The social, intellectual, physical, mental, and technical development of students is made possible through the guidance of teachers. Therefore, teachers hold a special place in society, as they are considered the makers of the future. The behavior of teachers significantly influences students, who often see their teachers as role models and strive to emulate them. However, various factors affect the job satisfaction of secondary school teachers. Similarly, different factors influence the job satisfaction of female teachers in secondary schools. To examine these effects, 120 male and female secondary school teachers from the Bijnor district were selected using a random sampling method. Standardized tools were used for data collection. For measuring job satisfaction, the scale developed by Dr. Pramod Kumar and D.N. Muthya was used. To assess anxiety, the scale by H. Sharma, R.L. Bhardwaj, and M. Bhargava was employed. For stress, the scale developed by Dr. Arun Kumar Singh, Dr. Ashish Kumar Singh, and Dr. Aparna Singh was used. The data obtained from these standardized instruments were analyzed using statistical methods, including the calculation of mean, standard deviation, and t-test. Based on the results, it was found that there is no significant difference in job satisfaction between male and female secondary school teachers across different categories.